CALCULUS ANURIA AND ITS REMEDY - ullah, Aman; Khan, Ghayyur; Lal, Shanti; Soomro, Muhammad Iqbal; Jalbani, Malik Hussain (Journal of Ayub Medical College Abbottabad, 2010)
Background: Urinary lithiases have been a major urological problem. The objective was to determine the out come of treatment for patients with calculus anuria. Methods: A descriptive study was conducted at Department of Urology Chandka Medical College Hospital, Larkana from March 2007 to April 2009. All patients with a diagnosis of calculus anuria of all ages and either sex were included in the study. Detailed history, physical examination and examination of genitourinary tract was performed. Investigations included complete blood examination, blood urea, serum creatinine, ultrasonography of KUB area, and X-Ray KUB. Results: Among the 66 patients the cause of anuria was bilateral obstruction by the calculi in 46 cases, unilateral obstruction with small/absent/ nephrectomised contralateral kidney in 20 cases. In most of the cases, ureteric catheterisation was done to relieve the obstruction. Five deaths were observed, despite emergency urinary diversion and appropriate treatment. Conclusion: Calculus anuria is a urological emergency. Prompt and early intervention can save the life of patient and prevent to develop chronic renal failure. Keywords: Anuria, calculus, and management